Über die Tätigkeit des Institutes für physikalische Chemie und Elektrochemie seiner Dozenten und tuirtenten - Bredig, Georg (1917)
Report on the activity of the Institute for Physical Chemistry and Electrochemistry written by Georg Bredig (1868-1944).
Keywords: Bredig, Georg, 1868-1944